On construction of asymptotic solution of the perturbed Klein-Gordon equation - Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider an application of the asymptotic method of nonlinear mechanics to the construction of an approximate solution of the Klein-Gordon equation.